Manajemen Cash Waqf sebagai Instrumen Alternatif SDG-1 "Ending Poverty" di Indonesia: Manajemen Cash Waqf sebagai Instrumen Alternatif SDG-1: “Ending Poverty” di Indonesia - Eugenia, Syaima; Paramita , Elvina Dian; Nurrahmah, Nisa; Beik, Irfan Syauqi (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2022)
Entering the era of the Sustainable Development Goals (SDGs), poverty has become a problem that cannot be fully resolved and is a top development priority. Indonesia is a developing country that has many problems related to poverty. The number of Muslim population in Indonesia which is the largest in the world become one of the one reason that shows that poverty in Indonesia can be overcome through productive cash waqf programs. However, currently the potential for cash waqf has not been optimized fully. This study aims to analyze the cash waqf management model in Indonesia and formulate a strategy for the use of cash waqf to alleviate poverty in the country. The method used is ANP-SWOT through literature studies and interviews with experts to validate the SWOT results and determine the order of priorities. The results show that the strategies that need to be carried out in order of priority, among others, are increasing the professionalism and competence of nazhir, optimizing digital technology in the distribution of cash waqf, maximizing cooperation with ulama, Islamic organizations, the business world, and government institutions in increasing socialization and literacy of cash waqf, improving productive waqf management programs, create a transparent, accountable, and integrated reporting system, optimize the use of digital technology in documenting waqf pledges, issuance of regulations that strengthen the utilization of cash waqf in productive economic programs, and invest cash waqf in investment portfolios that are able to provide high margin with well mitigated risk. Keywords: ANP-SWOT, cash waqf, ending poverty, nazhir, productive waqf.